The Arthurian book of days the greatest legend in the world retold throughout the year - Matthews, Caitlín 1952-; Matthews, John 1948- (Macmillan, 1990)
From the Dust Jacket: The legend of King Arthur, the Once and Future King, and the Knights of the Round Table is among the most powerful and durable of myths. It has been expanded and elaborated countless times, in many languages, and appeals as strongly to the romantic imagination of today as it did to the medieval audience for whom it was first set down. The Arthurian Book of Days is a unique way to enter this dramatic, colorful world. It can be consulted throughout the year, recounting the adventures of Arthur and his companions on a daily, seasonal, or annual basis. Many of the stories in the Arthurian cycle are commemorated on the day or days with which they are traditionally associated; each day throughout the year tells a different story or part of a story